Pengaruh Literasi Keuangan dan Cinta Uang Terhadap Perilaku Pengelolaan Keuangan Generasi Z di Indonesia: Pendapatan Sebagai Variabel Moderasi - Ningrum, Imas Dwi; Juniwati, Juniwati; Uray Ndaru Mustika; Anggraini Syahputri (Lembaga Pengembangan Kinerja Dosen, 2025)
Generation Z in the modern era faces financial challenges that could potentially affect economic well-being. This research will explore the influence of financial literacy and love for money on the financial management behavior of Generation Z in Indonesia, with income as a moderating variable. The research method used is quantitative with analysis through SMART PLS. The population of this study is Generation Z in Indonesia. The sample used consisted of 250 respondents. This study shows that financial literacy significantly influences financial management behavior, while love of money does not affect financial management behavior. Income, as a moderating variable, is able to significantly moderate the relationship between financial literacy and financial management behavior, but it cannot moderate the relationship between love of money and financial management behavior. The hope for future research is to be able to add factors that can influence financial management behavior.